COMPETITION BETWEEN ISLAMIC VS CONVENTIONAL MFI : ITS IMPACT ON CONSUMER’S ACCESS DECISION - DAVY HENDRI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
This study uses data from the survey IFLS-4 (Indonesia Family Live Surveys-wave 4) to analyze the impact of competition between lenders on client behaviour. IFLS-4 contains data on self-reported habits of community residents (312 community) decision to access to Islamic Micro Finance Institution (Islamic MFI), named Baitul Maal wat Tamwil (BMT). This data contains specific type of BMT’s location which could be accessed by community, with variously geographical distances. This data also is enriched by the presence of another type of conventional MFI. This study found that increased competition suggesting clients to change their behaviour. The presence of conventional MFI and theirs proximity as indicator of competition, very instrumental in determining access to BMT. Interesting finding, for religious type borrowers, they tend to sustain their access to BMT whose more far geographical distance, even conventional MFI presence inside their village. Thus, this study suggests that the expansion of financial inclusion strategy of Islamic MFI should also be specifically determined by behaviour of and the BMT’s location among the community.